Cloud-based Platform for Collaborative Business Process Management - Cocconi, Diego (2017)
With the wide adoption of the Internet, organizations establish collaborative networks to execute Collaborative Business Processes (CBPs). Current approaches of Process-Aware Information Systems (PAISs) to implement and execute CBPs have shortcomings: high costs and complexity of IT infrastructure to deploy the PAISs; poor support for autonomy, decentralization, global view of message exchange and peer-to-peer interactions; and rigid platforms for generating and deploying PAISs on-demand according with the CBPs agreed in collaborative networks. To overcome these issues, this work proposes a cloud-based platform for the management of CBPs. The platform provides cloud services that enable the generation and deployment on-demand of the PAISs required to implement the agreed CBPs, as well as the execution on-demand of CBPs by fulfilling the abovementioned issues. To deal with privacy issues, the platform can be deployed in private clouds. Elasticity is provided at the level of process instances and portability is also achieved.